Marie-Claude L’Homme. Lexical Semantics for Terminology: An Introduction. - Lü, Lingyun; Wang, Renqiang (Lexikos, 2020)
Review of Marie-Claude L’Homme. Lexical Semantics for Terminology: An Introduction.